Processes for regulating genetically modified and gene edited plants - John R Caradus (GM Crops & Food, 2023)
ABSTRACTInnovation in agriculture has been essential in improving productivity of crops and forages to support a growing population, improving living standards while contributing toward maintaining environment integrity, human health, and wellbeing through provision of more nutritious, varied, and abundant food sources. A crucial part of that innovation has involved a range of techniques for both expanding and exploiting the genetic potential of plants. However, some techniques used for generating new variation for plant breeders to exploit are deemed higher risk than others despite end products of both processes at times being for all intents and purposes identical for the benefits they provide. As a result, public concerns often triggered by poor communication from innovators, resulting in mistrust and suspicion has, in turn, caused the development of a range of regulatory systems. The logic and motivations for modes of regulation used are reviewed and how the benefits from use of these technologies can be delivered more efficiently and effectively is discussed.